Conducting Monetary Policy in South Asian Economies: An Investigation (The Pakistan Development Review, 2016)
Monetary policy which until recently aimed at targeting monetary aggregates has quietly given way to adjusting interest rates. Most of the Central Banks now focus on money reaction function that directly targets inflation or price level. This paper examines the way monetary policy is being conducted in the four major South Asian economies, namely, Bangladesh, India, Pakistan and Sri Lanka. The analysis is based on a variant of the Taylor rule framework. Using quarterly data over the period 1990Q1 to 2012Q4, the study finds that the monetary authorities in India, Pakistan and Sri Lanka have accommodated some degree of inflationary pressure, whereas Bangladesh has continuously smoothened interest rate while setting its monetary policy. Besides pursuing a mild monetary policy stance against inflation, India, Pakistan and Sri Lanka are also giving importance to foreign interest rate and real exchange rate movements to justify their relevance in monetary policy setting. However, the same has not been found to be true for Bangladesh. JEL Classification: E52, E58, E60 Keywords: Monetary Policy Rule, Central Banks, SAARC Countries